The effects of COVID‐19 on IBD prescribing and service provision in a UK tertiary centre. Issue 6 (5th December 2020) - Sharma, Esha; Meade, Susanna; D'Errico, Francesca; Pavlidis, Polychronis; Luber, Raphael; Zeki, Sebastian; Hill, Katie; Duff, Alexa; O'Hanlon, Dearbhaile; Tripoli, Sherill; Stanton, Anna; Caracostea, Andra; et al.
Abstract: Background: To quantify the effects of COVID‐19 on our inflammatory bowel disease (IBD) unit, including service provision, prescribing practices and use of therapeutic drug monitoring (TDM). Methods: We performed a single centre retrospective observational cohort study. Data was extracted from our IBD database, electronic patient records and radiology/endoscopy reporting systems between 16/3/20‐17/4/20 and the corresponding period in 2019. Results: A similar number of patients commenced biologic therapy before COVID‐19 (n = 37) and during the pandemic (n = 36). Patients in the pre‐COVID‐19 cohort were older (median 36 vs 29 years, P  = 0.009) with a longer median disease duration (9.3 vs 5.2 years, P  = 0.02). During COVID‐19 there was a nonsignificant increase in prescribing of vedolizumab (8/37, 22% vs 14/36, 39%, P  = 0.13) and a higher proportion of patients were anti‐TNF‐naïve (3/17, 18% vs 18/24, 74%, P  = 0.0004). There was a reduction in use of concomitant immunomodulators (22/29, 76% vs 4/34, 12%, P  < 0.0001) and increased biologic use in thiopurine‐naïve patients (3/37, 8% vs 15/36, 42%, P  = 0.001). Use of TDM fell by 75% (240 vs 59 tests). Outpatient appointments fell by 68% and were conducted via telemedicine. MRI scanning, endoscopy, luminal surgery and inpatient numbers fell by 87%, 85%, 100% and 82% respectively. IBD Clinical Nurse Specialist and Pharmacist helpline contacts increased by 76% and 228% respectively. Conclusions: We observed prescribing differences during COVID‐19, bypassing the initiation of immunomodulators and/or anti‐TNF therapy in favour of vedolizumab with a reduction in immunomodulator prescribing. We also observed a rapid reorganisation of service provision, including a shift towards telemedicine and online solutions.